Physical activity level and the risk of subjective health complaints in female university students - Razak, Norhanis Farina Abdul (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Most studies that were conducted about physical activity (PA) did not focus on its relationship with subjective health complaints (SHC) in the female university student population. In this study, the objective was to investigate the association between self-reported physical activity level and subjective health complaints in female university students. The present study is a cross-sectional study involving 205 female students aged between 18-29 years old from the three Universiti Sains Malaysia campuses: the Main Campus on the Island of Penang, the Health Campus in Kelantan, and the Engineering Campus in Nibong Tebal. The self-reported PA level was assessed using The Global Physical Activity Questionnaire (GPAQ) version 2 and the SHC was collected using a modified Adolescents and Surveillance System for The Obesity Prevention-Personal Information Questionnaire (ASSO-PIQ) that assessed the total score of eight common symptoms in the last six months, which consisted of headache, stomach-ache, backache, feeling low, feeling irritable or bad-tempered, feeling nervous or anxious, sleeping difficulties, and dizziness. A model of demographic characteristics was tested to examine risk factors for SHC. By testing using Pearson correlation, the results showed that the PA level was not associated in a linear relationship with SHC in students. However, moderate recreation and sedentary behaviour were associated in a linear relationship with SHC in students. As for demographic characteristics, marital status and employment status were associated in a linear relationship with SHC, whereby single students and unemployed students show a high total score of SHC. In conclusion, PA level does not influence SHC in students. Instead, marital status and employment were predictors of SHC. However, associations between PA and SHC were less apparent, whereby future studies should investigate the relationship between both variables in a diverse population and large sample size.